2010
DOI: 10.1111/j.1540-8175.2009.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Left Ventricular Dysfunction in Asymptomatic Severe Aortic Regurgitation Patients with Normal Ejection Fraction: A Combined Tissue Doppler and Velocity Vector Imaging Study

Abstract: VVI- derived strain imaging and TDI-derived IVA may be used as adjunctive, reliable, noninvasive parameters for evaluating subclinical ventricular dysfunction in patients with chronic, severe AR. This may help to identify patients for closer follow-up and to determine the need for surgery before developing irreversible, severe heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
0
27
1
Order By: Relevance
“…The fact that none of the variables was significantly altered in horses with moderate‐to‐severe AR suggests that the clinical use of TDI for the assessment of LV function in horses with AR may be limited. This seems to be in contrast to findings in people, where reduced S m , E m , and A m and prolonged IVCT m , IVRT m , and IMP m provide indices of subclinical LV dysfunction that may serve as prognostic indicators in asymptomatic patients with severe aortic regurgitation 11, 12, 13, 42, 43. However, it should be noted that classification of valvular regurgitation based on receiving chamber analysis of the regurgitant jet may not entirely reflect the hemodynamic status in individual horses.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The fact that none of the variables was significantly altered in horses with moderate‐to‐severe AR suggests that the clinical use of TDI for the assessment of LV function in horses with AR may be limited. This seems to be in contrast to findings in people, where reduced S m , E m , and A m and prolonged IVCT m , IVRT m , and IMP m provide indices of subclinical LV dysfunction that may serve as prognostic indicators in asymptomatic patients with severe aortic regurgitation 11, 12, 13, 42, 43. However, it should be noted that classification of valvular regurgitation based on receiving chamber analysis of the regurgitant jet may not entirely reflect the hemodynamic status in individual horses.…”
Section: Discussioncontrasting
confidence: 72%
“…Both in people and in small animals, the clinical applicability of TDI has been established and the modality has been successfully applied for the assessment of systolic and diastolic LV function and estimation of ventricular filling pressures 4, 5, 6, 7. It might have diagnostic and prognostic implications in cats and dogs with cardiomyopathies8, 9, 10 and aid in the diagnosis of subclinical LV dysfunction in asymptomatic human patients with aortic and mitral regurgitation 11, 12, 13…”
mentioning
confidence: 99%
“…It can detect even small changes in the contractile function and is well correlated with the invasive or noninvasive measures of LV dP/dt [13,17]. Therefore, IVA can be used as a valuable and easy parameter for the quantification of global systolic function in various cardiac diseases [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The chronic effects of abnormal loading from valvular disease on myocardial function may be difficult to detect by conventional means, and strain imaging may play a role (61)(62)(63)(64)(65)(66)(67). Delgado et al (62) demonstrated that patients with severe aortic stenosis and preserved EF exhibited decreased radial, circumferential, and longitudinal speckle tracking strain.…”
Section: Applications Of Strain Imaging For Effects Of Valvular Heartmentioning
confidence: 98%